Untypical symptoms for rather uncommon surgical entities: report of two rare cases of secondary intussusception in children (a case report) - Dimitrios, Godosis (Pan Afr Med J, 2020)
Intussusception in infants and children represents a relatively usual challenge for the pediatric surgeon. However, the incidence of lymphoma of the small intestine or inflammatory myofibroblastic tumor, acting as a lead point for invagination, are rather rare. We hereby present two cases of secondary intussusception, with the aforementioned lead points.